Islamic Values: Integration in Learning Mathematics and Science at Man 2 Level 2022/2023 Academic Year - Rizal, Suaif; Nahar, Syamsu; Al Farabi, Mohammad (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
Currently, in order to improve the quality of education, learning mathematics needs to undergo innovative changes in accordance with the times and technology. In addition, education must also build the values ​​and character of students through religious values. This research uses a qualitative approach with descriptive methods. The aim of the research is to describe Islamic values ​​and their integration into learning mathematics and science at MAN 2 Langkat in the 2022/2023 academic year. The research was conducted at MAN 2 Langkat, North Sumatra, with the research subjects being math and science teachers. Data was collected through observation, interviews, document studies, and literature. Data analysis was carried out by compiling, connecting, reducing, presenting, drawing conclusions, and verifying. The findings can be explained that Islamic values ​​in their integration into mathematics and science learning have been carried out well where they have been adapted to the curriculum and the school's vision and mission as outlined in the planning of relevant methods and media which are carried out from the beginning to the end of learning. The results of this study are expected to contribute to the development of learning that is integrated with Islamic values.